The Implementation of the Pancasila Student Profile Strengthening Project on the Theme of Sustainable Lifestyle in Rejang Lebong Elementary School - Gunawan, Guntur; Shintia, Esa Indy; Meldina, Tika; Yumiarty, Yuyun (Yayasan Corolla Education Centre, 2025)
The Pancasila Student Profile Strengthening Project at SDN 12 Rejang Lebong aims to address the lack of teamwork, creativity, and environmental concern among students. The project's focus is on Sustainable Lifestyle, emphasizing collaboration, ingenuity, and fear of God Almighty, along with admirable ethics. This study aims to examine the implementation of the project in Class V, focusing on faith, devotion to God Almighty, and noble morals. The research is both quantitative and descriptive, using data from VA and VB courses. The study found that Class V received an average of 4.47 with a TCR of 89.4%, categorized as very good. The project focused on the theme of sustainable lifestyle and cooperation, with a TCR of 84.1% and an average of 4.53. The Creative Dimension Pancasila Student Profile Strengthening Project, with the theme of Sustainable Lifestyle in Class V, earned an average of 4.50 with a TCR of 90.1%, placing it in the very excellent category. The project's implementation has been praised for its effectiveness in promoting Pancasila values and fostering cooperation among students. The project's success is attributed to its focus on promoting faith, piety, and noble morals in a sustainable lifestyle.